The intensity and effectiveness of the use of media viewer othello as mediation learning to master concept of count space operation at fifth grade students of sd negeri no. 08 koto barapak kecamatan bayang - Syafrizal Syafrizal (Jurnal Ilmiah Pendidikan Scholastic, 2018)
athematics is a very difficult subject to learn, that is not interesting compared to other subjects, and some of students like it, this is proven by the learning outcomes obtained by students is always low.To change the view is needed a way that can make students interested to learn math. Learning is a process that makes a person experience a change of behavior both in the form of knowledge and attitudes as a result of experience gained, thus the person learning is a person who experienced their own learning process.Mathematics learning should be packaged in a fun form and actively involve all students, so that students gain their own knowledge of what they must possess. This study aims to minimize students' learning difficulties in the field of mathematics studies, the activities are carried out in the learning process, by maximizing student activeness, teachers only as facilitators and motivators.In constructivist learning students learn by experiencing their own and build their own knowledge of experience experienced, and ultimately meaningful learning, if learning is meaningful, students' learning difficulties are resolved. This research was conducted in 3 cycles, each cycle consist of Planning, Action, Observation, Reflection.While the learning approach in this research using constructivist approach through Student Activity Sheet (LKS) that researchers make in a structured so that students can build their own knowledge by way of completing LKS in groups. The data in this study were obtained by test scores, observations and questionnaires, where the function of the data that has been obtained as follows: (1) Value test to determine the success of student learning to understand the material being taught.(2) Observation to determine the activity of students in learning, and a questionnaire to determine the students' response to learning with a constructivist approach. Based on the observation result indicated by the acquisition value, the average yield is less;the average value only reached 5.74%.The highest percentage of five is 33.33% of the number of students.From the data analysis, the average value and observation result that can be interpreted as follows: the average value of pre test is 5.03 and the average value of post test is 6, 92. This average yield has not reached 7.5 in line with complete learning.This progress can also be seen from the teacher's average performance.In the first action learning gets an average of 3.3 with a maximum score of five.In the second action the average score rose to 3.7.This is an increase of 0.4.From the average data the value can be interpreted as follows;an increase in the result of the average value of pre test results and the average post test with a new average indicates 7.4. This level of mastery has not reached 7.5 in accordance with the principle of complete learning but has shown success with an increase in the average result of the first action 6.92 and the second action 7.19.This is an increase of 0.27. Using the Viewer Tool Othello in class V SDN No.08 KotoBerapak Kecamatan Bayang, Kabupaten Pesisir Selatan, in the first half proved to be an effective and efficient media in Teaching and Learning.This is evidenced by the increase in student learning outcomes from the first view to the third view. The learning outcomes achieved from the first to the third learning acts show an increase in the average score, indicating the success of mathematics learning with visual aids. In the final post test the average score of learners in the subject area reaches 7.79. It shows a high level of mastery and reaches the level of mastery learning (master learning).